A responsabilidade penal dos diretores de empresas, em desastres ambientais e homicídios, a partir da teoria da ação significativa - Moreira Junior, Syrio Cavagnoli (2021)
This work aims to analyze the criminal liability of company directors, as well as how to discuss eventual intent and conscious guilt, through humanistic understanding Vives Antón's Theory of Meaningful Action, taking as an example the concrete case of Brumadinho, with crimes against life and environmental, through research bibliographical. The evolution of society occurs through the intensification of flows of people, information, energy and goods. The way human beings relate with the environment, objectifying its resources and using them in a unconscious, shows us results such as animal and plant species being extinct, environmental refugees, depleted natural resources, deforestation, excessive pollution, global warming and disasters. As a result, the environment suffering degradation of unimaginable proportions with the process of globalization. So that this scenario does not intensify in an uncontrolled manner, the There is criminal liability that differs from a natural person from a legal entity. THE This work is aimed at the criminal liability of individuals, since for a legal entity to exist it is made up of natural persons and that, the penalty for legal entities is not yet fully regulated, giving room for some cases not to receive accountability. The most serious crimes common issues involving companies are economic and environmental, in this specific case used in this work there were crimes against life, which makes it even more relevant to criminal liability. Life, considered as an object of right and the most valuable asset in life, it is made up of material and immaterial elements and constitutes the primary source of all other legal assets. Both life and the environment environment are fundamental human rights, actions that violate them are characterized as crimes. Crime, the main object of study in Criminal Law, Since its inception, it has been undergoing changes depending on the times, as scholars realize that new concepts can bring more justice. In this way, we intend to briefly review some concepts and changes coming from new perspectives triggering new theories - with some points common among all, of interpreting the illicit fact reaching the Theory of Action Meaningful that aims at humanistic understanding, connected to the context social environment in which the action develops, proposing a new evaluative claim of the crime, formed by four claims: claim of relevance, of illegality (fitting in this deceit and imprudence), of reproach and the need for punishment and using it as concrete case to interpret it, the case of Brumadinho, with crimes against life, against bodily integrity and individual and collective environmental assets. Such analysis starts from knowing the context of the action, not just the result of the action to that criminal liability comes as close as possible to justice. The present work does not aim to find those responsible for the case, just use theory to discover, based on the context in which the case occurred, the degree of responsibility penalty that can be attributed to company directors.